Tualang honey consumption enhanced hippocampal pyramidal count and spatial memory performance of adult male rats - Mohd Amiruddin Kamarulzaidi; M. Y. Zulkifli Mohd. Yusoff; Abdul Majid Mohamed; Durriyyah Sharifah Hasan Adli (Universiti Kebangsaan Malaysia, 2016)
As a natural anti-oxidant source, Tualang honey, produced by wild bees nesting on the Tualang tree (Koompassia excelsa) is expected to have positive influence on health, including memory. This study investigated the effect of Tualang honey on the cell count of memory formation related hippocampal pyramidal neuron and on spatial memory performance (SMP) of rats using the radial arm maze (RAM). Sprague Dawley male rats (n=24), 7-8 weeks old were divided into two groups; experimental group group force-fed 1 mL/100 g body weight with 70% honey (HG); and the control group with 0.9% saline (CG) for 12 weeks. Nissl staining technique (with cresyl violet) was employed for neurohistological analysis of the hippocampal tissue. Six randomly selected rats from each group were used for the neuronal soma counting of pyramidal cell layer CA1, CA3a and CA3c regions. Two-way ANOVA analysis showed positively significant differences between treatment and control groups for SMP comparison of working memory and reference memory components, as well as the number of pyramidal neurons. Hence, this positive effects of Tualang honey, as demonstrated behaviorally and neurohistologically, supported report that Tualang honey could improve memory and deter hippocampal morphological impairments; possibly due to its high anti-oxidant properties.